From Monologue to Dialogue: How Classroom Talk Shapes Communicative Learning in ELT - Sultana, Sadia; Usha, Ummay Habiba (IJLHE: International Journal of Language, Humanities, and Education, 2026)
This study examines the role of classroom discourse in shaping communicative learning in Bangladeshi English Language Teaching (ELT) classrooms. Grounded in sociocultural and interactionist perspectives, the study adopts a mixed-methods design to explore both discourse patterns and participants’ perceptions. Data were collected from five secondary and tertiary classrooms involving approximately 150 students and 30 teachers through classroom observations, questionnaires, interviews, and pre- and post-task assessments. The findings reveal that classroom interaction remains predominantly monologic, with Teacher Talking Time significantly exceeding Student Talking Time. Despite this, both students and teachers demonstrate a strong preference for dialogic interaction. Quantitative results indicate that students feel more confident and engaged during pair and group activities, while qualitative data highlight persistent barriers such as fear of making mistakes, large class sizes, and exam-oriented instruction. Teachers acknowledge the importance of communicative competence but report challenges in implementing Communicative Language Teaching (CLT) due to contextual constraints, including limited time and institutional expectations. The study identifies a clear gap between communicative pedagogical ideals and classroom realities, resulting in a hybrid instructional environment where Grammar-Translation Method (GTM) practices coexist with CLT principles. These findings suggest that enhancing dialogic classroom talk is essential for fostering learners’ communicative competence. The study contributes to the literature by highlighting classroom discourse as a critical mechanism of learning rather than a peripheral feature of instruction. It also underscores the need for pedagogical and structural reforms to support sustainable dialogic practices in ELT contexts.